Quem tem medo do Queermuseu? a associação da arte com a pedofilia na CPI dos maus-tratos - Pinto, Bryan Henrique (Universidade Federal de São Carlos, 2023)
The present work aims to analyze the discourse at the meetings of the Parliamentary Commission of Inquiry into Mistreatment (CPIMT) regarding the arts. The exhibition “Queermuseu – Cartografias da Diferença na Arte Brasileira”, and the performance “La Bête” starring the artist Wagner Schwartz, both accused on social networks of pedophilia, become CPI material. Therefore, we seek to understand how art exhibitions became the subject of a CPI, analyzing the discourse, verifying whether there was a process of censorship and artistic persecution, and also whether such discourse would be a transnational process of mobilizing the contemporary monster, the pedophile. , in order to bar sexual and reproductive rights, creating a “gender ghost”. For this theoretical undertaking, we intend to use Foucault's formulations on discourse methodologically, as well as the theoretical framework of Queer Theory to help us understand the plot of the CPIMT, the discourses that permeated during the meetings.
Who's afraid of the Queermuseum? the association of art with pedophilia in the CPI of mistreatment
Keywords: Queermuseu; Sexualidade; Pedofilia; CPI dos maus tratos; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS